Degrowth as an Alternative to the Growth Hegemony: Discussions Based on City, Space and Planning - Atlar, Ozge Gurbuz; Dincer, Iclal Sema (KARE PUBL, 2024)
Infinite growth is no longer sustainable in today's conditions where the planet is based on its ecological limits. Growth hegemony not only causes ecological destruction, but also creates social, economic and spatial inequalities. Planning discipline has a regulatory role in ensuring social and spatial organization. This situation requires and enables a new understanding both in the economic system and in the planning discipline due to its regulatory position. This study is about searching for an urban imagination other than growth-oriented planning. First of all, the emergence of degrowth approach and its theoretical framework are explained. Afterwards, the approaches to city, space and planning in degrowth literature were examined with a bibliometric analysis using a formula created in Web of Science. Based on the results obtained, the relationship between planning and degrowth has been evaluated in terms of its potentials and dilemmas in four categories: Opportunities, Alliances: Institutions and Commons, Conflicts: Scale and Urbanization and Method: Politics and Planning Paradigm, which are produced from the dynamics of the relationship itself.
Keywords: Growth hegemony; ideology; urban politics; degrowth; planning; URBAN GOVERNANCE; SUSTAINABILITY; TRANSFORMATION; TRANSITION; STRATEGIES; CITIES; Public Administration